Cellular immunotherapy for medulloblastoma. Issue 4 (11th October 2022) - Schakelaar, Michael Y; Monnikhof, Matthijs; Crnko, Sandra; Pijnappel, Emma W; Meeldijk, Jan; ten Broeke, Toine; Bovenschen, Niels
Abstract: Medulloblastoma (MB) is the most common malignant brain tumor in children, making up 20% of all primary pediatric brain tumors. Current therapies consist of maximal surgical resection and aggressive radio- and chemotherapy. A third of the treated patients cannot be cured and survivors are often left with devastating long-term side effects. Novel efficient and targeted treatment is desperately needed for this patient population. Cellular immunotherapy aims to enhance and utilize immune cells to target tumors, and has been proven successful in various cancers. However, for MB, the knowledge and possibilities of cellular immunotherapy are limited. In this review, we provide a comprehensive overview of the current status of cellular immunotherapy for MB, from fundamental in vitro research to in vivo models and (ongoing) clinical trials. In addition, we compare our findings to cellular immunotherapy in glioma, an MB-like intracranial tumor. Finally, future possibilities for MB are discussed to improve efficacy and safety.